X+13+3x=-34-3x-39

Simple and best practice solution for X+13+3x=-34-3x-39 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+13+3x=-34-3x-39 equation:


Simplifying
X + 13 + 3x = -34 + -3x + -39

Reorder the terms:
13 + X + 3x = -34 + -3x + -39

Reorder the terms:
13 + X + 3x = -34 + -39 + -3x

Combine like terms: -34 + -39 = -73
13 + X + 3x = -73 + -3x

Solving
13 + X + 3x = -73 + -3x

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-13' to each side of the equation.
13 + X + -13 + 3x = -73 + -13 + -3x

Reorder the terms:
13 + -13 + X + 3x = -73 + -13 + -3x

Combine like terms: 13 + -13 = 0
0 + X + 3x = -73 + -13 + -3x
X + 3x = -73 + -13 + -3x

Combine like terms: -73 + -13 = -86
X + 3x = -86 + -3x

Add '-3x' to each side of the equation.
X + 3x + -3x = -86 + -3x + -3x

Combine like terms: 3x + -3x = 0
X + 0 = -86 + -3x + -3x
X = -86 + -3x + -3x

Combine like terms: -3x + -3x = -6x
X = -86 + -6x

Simplifying
X = -86 + -6x

See similar equations:

| 5+x+9=21 | | m(x)=3x-4 | | 2n+3n-10=40 | | -7-2=7(x+8) | | 8m-2(m-3)= | | y=61+-1x | | 5n+n+10=28 | | 2x+1-x+2= | | f(x)=x^2+9x-1f(x+6) | | 9x+6=4x+101 | | 8(2K-1)=4k-28 | | -5=-2+l | | 9(2y-8)-(2y+2)= | | f(x+6)=x^2+9x-1 | | (176-y)=(115+x) | | 5n-n+5=13 | | 4x^2+y^2+2y=0 | | -3=m-3 | | 3=l-5 | | 4n-2n+10=22 | | -9+y=7 | | f(x)=x^2+9x-1 | | 1.05t+0.63=-0.07t | | 4x+2(8)=4x(9) | | 10n+2=22 | | 13-6b=3+11b | | 9n+18=36 | | (99+x)=(176+y) | | -9(x+3)+3x+6=5x+9 | | 6.75t+7=15.5t+14 | | 4568b-4=7 | | -v+2=3 |

Equations solver categories